SpaceOps 2006 Conference 2006
DOI: 10.2514/6.2006-5786
|View full text |Cite
|
Sign up to set email alerts
|

Mars Reconnaissance Orbiter Ka-Band (32 GHz) Demonstration: Cruise Phase Operations

Abstract: The X-band (8.41 GHz) frequency currently used for deep space telecommunications is too narrow (50 MHz) to support future high rate missions. Because of this NASA has decided to transition to Ka-band (32 GHz) frequencies. As weather effects cause much larger fluctuations on Ka-band than on X-band, the traditional method of using a few dBs of margin to cover these fluctuations is wasteful of power for Ka-band; therefore, a different operations concept is needed for Ka-band links. As part of the development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…During cruise the MRO Ka‐band system set a new record for the rate of data return from deep space as part of in‐flight testing. Detailed analysis of Ka‐band performance during the MRO cruise is presented elsewhere [ Shambayati et al , 2006, 2007].…”
Section: Mro Mission Objectivesmentioning
confidence: 99%
“…During cruise the MRO Ka‐band system set a new record for the rate of data return from deep space as part of in‐flight testing. Detailed analysis of Ka‐band performance during the MRO cruise is presented elsewhere [ Shambayati et al , 2006, 2007].…”
Section: Mro Mission Objectivesmentioning
confidence: 99%
“…These passes indicated that while the blind-pointing of the ground antennas were adequate they needed further improvements. In addition, the monopulse system was deemed difficult to operate due to both its complexity and the lack of familiarity of the complex personnel with it [83]. Ka-band Doppler and 2-way ranging were also analyzed for these passes [84].…”
Section: Dsn Developments Deep Space 1 and Cassini: 1997 To 2002mentioning
confidence: 99%
“…MRO also includes a technology demonstration experiment consisting of a Ka‐band transponder on the spacecraft that produces an RF downlink at a frequency of 32.2 GHz [ Shambayati et al , 2006]. The Ka‐band subsystem has a 35‐Watt TWTA to amplify its signal so that it can be downlinked to DSN antennas that have been modified to receive at that frequency.…”
Section: Tracking Of the Mars Reconnaissance Orbitermentioning
confidence: 99%